PENGARUH PENERAPAN IFRS BERDASARKAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN INTELECTUAL CAPITAL - Sari Rahmadhani; Ita Nur Rahmawati (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This study aims to test the disclosure of Intellectual Capital in theperiod before and after the full adoption of IFRS in Indonesia. Adoption ofpeuh in Indonesia has been in effect since 2012. Testing of Companycharacteristics based on company age in operation, firm size and leveragelevel. The sample used in this study was taken from 96 companies that meetthe criteria ratio of capital expenditure above 8. The results show that theold company higher in the disclosure of Intellectual capital after the fulladoption period. While there is no disclosure of intellectual capital of largecorporations and small companies before and after the full adoption period ofIFRS. The disclosure of intellectual capital in high leverage companies andlow leverage companies in both absolute and statistically is not different.